2008
DOI: 10.1021/jp804757n
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rotator Glass in Lead(II) Pentanoate: Calorimetric and Spectroscopic Study

Abstract: Lead(II) pentanoate was studied by DSC, XRD, and FTIR and solid state CP/MAS-NMR spectroscopies. A transition from the crystal to the intermediate phase, at T(ss) = 328.2 +/- 0.6 K, with delta(ss)H = 8.8 +/- 0.1 kJ x mol(-1), and a melting at T(f) = 355.6 +/- 0.3 K, with delta(f)H = 12.6 +/- 0.1 kJ x mol(-1), were observed on first heating. The thermal and structural behavior of the lead(II) pentanoate shows as a link between those of the shorter and longer members of the previously studied lead(II) alkanoate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 56 publications
(87 reference statements)
1
28
0
Order By: Relevance
“…Typically, the hydrocarbon chains in the lamellar are packed in the fully extended all-trans conformation. This was proven by a number of authors [20,27,31] on the basis of IR data as outlined in the forgoing.…”
Section: Infrared Spectroscopymentioning
confidence: 81%
See 4 more Smart Citations
“…Typically, the hydrocarbon chains in the lamellar are packed in the fully extended all-trans conformation. This was proven by a number of authors [20,27,31] on the basis of IR data as outlined in the forgoing.…”
Section: Infrared Spectroscopymentioning
confidence: 81%
“…Such parameters were useful in presenting a picture of the molecular and lattice packing of these compounds. Further calculations carried out by several authors [18,27,31] have shown that comparison of the d-spacing, d exp , which represents the distance between successive metal planes, and the calculated molecular…”
Section: Structural Information From Powder X-ray Diffractionmentioning
confidence: 99%
See 3 more Smart Citations